2019
DOI: 10.1089/bio.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Tissue Microarrays from Banked Human Formalin-Fixed Paraffin Embedded Tissues in the Cancer Research Setting

Abstract: The tissue microarray (TMA) is a powerful tool for cancer biomarker discovery and validation. Tens to hundreds of samples can be evaluated simultaneously for molecular marker status at the protein or nucleic acid level. Although fully automated or semiautomated technologies for TMA creation provide excellent precision with respect to core transfer, they do not obviate the need for technical expertise to successfully generate highquality TMA blocks and derivative sections. We have leveraged our expanding bank o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Numerous tissue samples from several types of cancer can be examined simultaneously on one slide. This process preserves tissue as well as reduces the reagent cost of detecting a single biomarker 9 . TMAs can be used in many types of human cancer investigations, including breast cancer 1 , prostate cancer 10 , and colon cancer 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous tissue samples from several types of cancer can be examined simultaneously on one slide. This process preserves tissue as well as reduces the reagent cost of detecting a single biomarker 9 . TMAs can be used in many types of human cancer investigations, including breast cancer 1 , prostate cancer 10 , and colon cancer 11 .…”
Section: Discussionmentioning
confidence: 99%
“…After testing three sets of conditions, we determined that the optimal protocol involved 24 h of incubation at 43°C, then cooling down to 4°C for 1 h. Our optimal temperature and duration were different from a previous study; Sexton et al . 9 showed that the optimal protocol for core integration with the template block is performing repetitive cycles of 1-h incubations at 37°C and 4°C, which was considered a time-consuming process 9 . This step is very necessary for the block preparation and successful sectioning.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, for our TMA, all core annotations were reviewed by reference sarcoma pathologists. Next, variation can occur in localizing needle to punch tissue out based on the annotations on the H&E slides, and the shape of donor tissue may slightly deform during sections or heating/cooling of FFPE blocks [36]. To Sarcoma improve the precision of tissue retrieval, digital annotations and fully automated tissue microarrayer were applied for a better alignment between annotated images and donor blocks.…”
Section: Mhc I/mhc Ii/dapi (Cycle 6)mentioning
confidence: 99%